Career counselling in South African institutions of higher learning in the 21st century: Re-discovering the potential of qualitative approaches - Maree, Kobus (South African Journal of Higher Education, 2016)
In South Africa, as in many other countries, concern is growing about rising unemployment. The impact is felt not only on the lives of millions of people but also on the national economy where the required 6% economic growth rate has not been achieved. A review of the literature on the South African tertiary training system reveals that inadequate career counselling tends to reinforce the low social and economic position of poor and marginalised people in South Africa. Very few disadvantaged students ever receive adequate career counselling at school and often arrive at institutions of higher learning without a clear sense of what their prospective careers will entail. Intervention programmes to correct this situation have not achieved the state's goals in this regard. Much has been written about the endemic problems in tertiary training that have played a key role in students' failure to achieve and design successful lives. Consensus opinion seems to be that whereas counsellors and lecturers need to be guided with vision and motivation, students need to be provided with adequate career counselling to give them a clear sense of the future, knowledge about what career to pursue, reasons for working hard and realising their potential, and guidelines to help them design successful lives and holding environments.